Strategies For Improving The Quality Of Public Services Through Village Digitalization: A Case Study In Sohuwe Village - Warahuwena, Lenci Yakoba; Sipahelut, Semuel Willem; Wokanubun, Paulina (HIPOTESA - Jurnal Ilmu-Ilmu Sosial, 2025)
This study aims to analyze strategies for improving the quality of public services through digitalization in Sohuwe Village, East Taniwel District, West Seram Regency. Digitalization is seen as a solution to the low efficiency, transparency, and accessibility of village public services, which are still predominantly manual. This research employs a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The results indicate that digitalization has not been optimally implemented due to infrastructure constraints, low digital literacy among village officials and residents, and a lack of technological devices. However, there is a strong commitment from the village government to accelerate digital transformation. Strategic recommendations include improving digital infrastructure, enhancing digital literacy training, providing technological equipment, and strengthening multi-stakeholder collaboration, including through CSR programs. These strategies are expected to foster faster, more efficient, and more transparent public services.